Unveiling Kikuchi-fujimoto disease in systemic lupus erythematosus: Case report and comprehensive review of literature (Indian Journal of Case Reports, 2024)
Kikuchi-Fujimoto disease (KFD) also referred to as histiocytic necrotizing lymphadenitis is an uncommon, non-malignant condition with unknown etiology. The diagnosis of KFD was hampered by the similarity to lymphoma, viral infections, and other autoimmune diseases. We present a 43-year-old female with a history of systemic lupus erythematosus (SLE) with a history of low-grade fever for 10 days, associated with chills, rigors, and pain over the posterior aspect of the neck with swelling. An excisional biopsy of the cervical lymph node confirmed the diagnosis of KFD. KFD should be considered in patients with SLE who presented with cervical lymphadenopathy and systemic symptoms. KFD is often confused with malignancy/tubercular lymphoma which requires costly diagnostic techniques and medications, but KFD is a self-limited condition.